2013
DOI: 10.1073/pnas.1302078110
|View full text |Cite
|
Sign up to set email alerts
|

First look at changes in flood hazard in the Inter-Sectoral Impact Model Intercomparison Project ensemble

Abstract: Climate change due to anthropogenic greenhouse gas emissions is expected to increase the frequency and intensity of precipitation events, which is likely to affect the probability of flooding into the future. In this paper we use river flow simulations from nine global hydrology and land surface models to explore uncertainties in the potential impacts of climate change on flood hazard at global scale. As an indicator of flood hazard we looked at changes in the 30-y return level of 5-d average peak flows under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
240
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(262 citation statements)
references
References 34 publications
(24 reference statements)
15
240
1
2
Order By: Relevance
“…Pappenberger et al 2012) may give different indications of regional exposure to flood risk. Dankers et al (2013) show how projected changes in flood magnitudes can vary considerably between different global hydrological models, largely due to their different representation of evaporation and snowmelt processes. New attempts to estimate current global flood risk (e.g.…”
Section: Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pappenberger et al 2012) may give different indications of regional exposure to flood risk. Dankers et al (2013) show how projected changes in flood magnitudes can vary considerably between different global hydrological models, largely due to their different representation of evaporation and snowmelt processes. New attempts to estimate current global flood risk (e.g.…”
Section: Caveatsmentioning
confidence: 99%
“…Bell et al 2007;Prudhomme et al 2003;Milly et al 2002;Lehner et al 2006;Hirabayashi et al 2008;Dankers and Feyen 2009;Dankers et al 2013). A key conclusion of such studies is that the projected effects of climate change on the flood hazard may be very substantial, but are very dependent on climate scenario.…”
mentioning
confidence: 99%
“…In this article, the climate projections are bias corrected against observations (Hempel et al, 2013), and the value of them has also been well demonstrated in a number of recent studies (e.g. Dankers et al, 2014;Elliott et al, 2014;Haddeland et al, 2014;Leng and Tang, 2014;Piontek et al, 2014;Prudhomme et al, 2014;Schewe et al, 2014). Moreover, the impact model (i.e.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…drought/floods) have applied the so-called fixed threshold method (e.g. Hirabayashi et al, 2013;Dankers et al, 2014;Prudhomme et al, 2014). Typically, characteristics of extremes in the 21st century are identified by using the threshold derived from the fixed historical period (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the impact of floods has drastically increased worldwide (European Environment Agency, 2006;Di Baldassarre et al, 2010;Aerts et al, 2014;Dankers et al, 2014). Flood events in Europe, such as the 2002 Elbe floods and the 2007 UK floods, are considered national crises and are estimated to have caused around 15 and 6.5 billion Euro of damage respectively (European Environment Agency, 2006).…”
Section: Flood Forecasting and Early Warning Systemsmentioning
confidence: 99%